Evaluation of the long-term performance of stabilized sandy soil using binary mixtures: A micro- and macro-level approach. (10th September 2020) - MolaAbasi, Hossein; Naderi Semsani, Safoura; Saberian, Mohammad; Khajeh, Aghileh; Li, Jie; Harandi, Mohammad
Abstract: The growing trend towards cement production for civil engineering applications has caused many environmental concerns, which can be addressed by the partial or total replacement of cement in civil construction projects. In the current study, the effect of partial cement replacement with zeolite (Z) on the behavior of poor-graded sandy soil was evaluated by means of a series of unconfined compression, durability (wetting-drying cycles), and undrained triaxial (CU) tests, as well as SEM and XRD analyses, and considering curing times ranging from 3 to 90 days. Based on the results, the incorporation of zeolite up to 30% cement replacement in the cemented sand increased the unconfined compressive strength (UCS) and reduced the accumulated loss of mass (ALM), and, hence, enhanced the strength and durability. However, the higher adoption of zeolite decreased the UCS and durability. Therefore, 30% of zeolite replacement was the optimum state. Moreover, the key parameter of active composition (AC) was successfully employed to estimate the UCS and ALM through a power relationship. The triaxial test results proved that the addition of zeolite led to an increase in the peak and residual shear strengths (qmax and qres ) and axial strains at qmax (ϵf ), and improved the ductility of the samples by reducing the brittle index (IB ). It also enhanced the other properties, including stiffness (E50 ), friction angle ( ϕ ), and cohesion (C). Ultimately, the SEM and XRD analyses confirmed that the inclusion of zeolite in the cemented sand resulted in the formation of more ettringite crystals and calcium silicate hydrate (C–S–H), which led to higher strength. Finally, it was concluded that zeolite could effectively supplant part of the cement in sand stabilization for geotechnical applications.